Experiences of obstetric nurses and midwives receiving a perinatal bereavement care training programme: A qualitative study - Qian, Jialu; Chen, Shuyi; Jevitt, Cecilia; Sun, Shiwen; Wang, Man; Yu, Xiaoyan (Frontiers in Medicine, 2023)
Aim: To explore obstetric nurses and midwifery professionals’ experiences with the Perinatal Bereavement Care Training Programme (PBCTP) after implementation. Design: A qualitative descriptive design was used. Method: This qualitative study was conducted at a tertiary level maternity hospital in China. The PBCTP was implemented at Women’s Hospital School of Medicine, Zhejiang University from March to May 2022. A total of 127 nurses and 44 midwives were invited to participate in the training. Obstetric nurses and midwives studied a 5-module training programme comprised of 8 online theoretical courses and submitted a reflective journal after each session. Semi-structured interviews were conducted with 12 obstetric nurses and 4 midwives from May to July 2022 as a post-intervention evaluation. Thematic analysis was used in data analysis. Findings: A total of 16 participants in this study ranged in age from 23 to 40 years (mean age [SD], 30 [4] years). Six main themes within participants’ experiences of PBCTP intervention were identified: participants’ aims of undertaking the training; personal growth and practice changes after training; the most valuable training content; suggestions for training improvement; directions for practice improvement; influencing factors of practice optimisation. Conclusion: Nursing and midwifery professionals described the PBCTP as satisfying their learning and skills enhancement needs and supporting positive changes in their care providing for bereaved families. The optimised training programme should be widely applied in the future. More efforts from the hospitals, managers, obstetric nurses, and midwives are needed to jointly contribute to forming a uniform care pathway and promoting a supportive perinatal bereavement care practice.